Discrepancy in Sterol Usage between Two Polyphagous Caterpillars, Mythimna separata and Spodoptera frugiperda - Rui Tang; Junhao Liang; Xiangfeng Jing; Tongxian Liu (Insects, 2022)
Insects are sterol auxotrophs and typically obtain sterols from food. However, the sterol demand and metabolic capacity vary greatly among species, even for closely related species. The low survival of many insects on atypical sterols, such as cholestanol and cholestanone, raises the possibility of using sterol-modified plants to control insect herbivore pests. In this study, we evaluated two devastating migratory crop pests, Mythimna separata and Spodoptera frugiperda, in response to atypical sterols and explored the reasons that caused the divergences in sterol nutritional biology between them. Contrary to M. separata, S. frugiperda had unexpectedly high survival on cholestanone, and nearly 80% of the individuals pupated. Comparative studies, including insect response to multiple diets and larval body sterol/steroids analysis, were performed to explain their differences in cholestanone usage. Our results showed that, in comparison to M. separata, the superiority of S. frugiperda on cholestanone can be attributed to its higher efficiency of converting ketone into available stanol and its lower demand for sterols, which resulted in a better survival when cholesterol was unavailable. This research will help us to better understand insect sterol nutritional biology and the potential of using atypical sterols to control herbivorous insect pests.